2018
DOI: 10.1177/2192568218795867
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Cost-Effectiveness of Spinal Versus General Anesthesia for Lumbar Spine Surgery in Various Hospital Settings

Abstract: Study Design: Retrospective chart review. Objective: To determine the relative cost-effectiveness of spinal anesthesia and general anesthesia for lumbar laminectomy and microdiscectomy surgery performed in an academic versus private practice hospital setting. Methods: The authors retrospectively reviewed charts of 188 consecutive patients who underwent lumbar laminectomy or microdiscectomy by a single surgeon from 2012 to 2016 at either an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Mathew et al 16 found less expenditure in SA for a similar lumbar spine surgery under GA and we had the same experience of overall 10% cost saving in SA group.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Mathew et al 16 found less expenditure in SA for a similar lumbar spine surgery under GA and we had the same experience of overall 10% cost saving in SA group.…”
Section: Discussionsupporting
confidence: 69%
“…Spinal anaesthesia for lumbar spine instrumented fusion surgeries leads to less anaesthesia procedure time, overall operating room, PACU time. 16,17 The cost of consumables and medicines used in SA is less than in case of GA. We have seen from the overall expenditure that in case of SA there is average 10% of cost reduction. Without compromising the outcome SA is clearly most cost effective alternative to GA in lumbar spine instrumented surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spinal anesthesia is considered to be less cost-effective for some procedures, such as inguinal hernia repair [13] or lumbar spine surgery [14]. There is no morbidity or mortality evidence in favor of either spinal anesthesia or general anesthesia [15].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have suggested that anesthetic technique may impact surgical outcomes due to the known associated complications and side-effects of general anesthesia [ 11 , 12 , 22 , 27 ]. Additionally, it is possible that anesthetic technique may influence a surgeon's decision-making intraoperatively due to the added factor of patient discomfort that must be considered in awake spinal surgery.…”
Section: Discussionmentioning
confidence: 99%